RUSSIA’S FOREIGN POLICY IN THE EVALUATION OF THE LEADERS OF THE NON-SYSTEM OPPOSITION: A COMPARATIVE ANALYSIS - N. A. Ponomarev; A. A. Mailis (Сравнительная политика)
After the reunification of the Crimea with Russia, the perception of the foreign policy course turned into a universal marker, serving to identify membership in specific political groups. Differences in assessments of Russian foreign policy became one of the reasons for the split within the non-system opposition. The positioning of Russian foreign policy has become a factor determining the prospects for expanding supporters of various opposition structures. The purpose of this study is to identify common and specific elements in assessments of Russia's foreign policy for the period 2014-2017 by leaders of non-system opposition. The empirical basis of the work was formed by summarizing the materials of public speeches of 13 politicians belonging to different segments of the non-system opposition. The perception of the foreign policy of official Moscow is assessed through the prism of positioning the situation around the Crimea, Donbass and Syria. Based on the findings, it was concluded that within the non-system opposition, as well as within its individual groups, a joint assessment of Russia's foreign policy was not worked out. Similarly, alternative scenarios of foreign policy, offered by the opposition, differ substantially. There are certain consensus points. So, with rare exceptions, the oppositionists condemn Russia's interference in the Syrian conflict in any form, like the idea of the need for an unconditional return of the Crimea to Ukraine. The common point in assessing the Kremlin's foreign policy is accusations of ignoring the state of the Russian economy and seeking to use local conflicts as a means of diverting citizens' attention from domestic problems. However, liberals, representatives of nationalists and the conditional «patriotic wing» differ significantly in the perception of the situation in the Donbass, in many respects in principle. Differences in foreign policy issues may serve as an obstacle to the consolidation of both the entire non-system opposition and its individual, ideologically close groups. At the same time, we can note favorable conditions for creating situational alliances between representatives of different ideological nominations.